Seven Principles of Digital Business Strategy. - McKeown, Niall; Durkin, Mark (Digital and social media marketing and advertising collection., 2017)
If we are creating most of our competitive advantage at the strategic planning stage, why are we spending so little time on this and so much time on technology? This book is not about why you should digitally transform and become more strategic, it's about how. It lays out the steps that must be taken, the data that should be used, and the decision tree to be followed. Following the principles laid out in this book allows organizational leaders, marketers, and technologists to talk at a high strategic level without getting bogged down in the tactics and delivery that consumes most of the time, attention, and activity in the modern workplace. Use The Seven Principles of Digital Business Strategy to define the direction of travel for your business in today's digital economy.